2009
DOI: 10.1016/j.archger.2008.02.015
|View full text |Cite
|
Sign up to set email alerts
|

The home is the hub of health in very old age: Findings from the ENABLE-AGE Project

Abstract: The aim was to explore health in relation to the home as experienced by very old, singleliving Swedish people. Applying a grounded theory approach, 40 men and women aged 80-89 were interviewed in their own homes. Data analysis revealed the main theme "The home is the hub of health", comprising two categories, "The home as support for health", and "Having an inner driving force to maintain health". Health was described as being active and participating, and during the aging process the home became an increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 44 publications
(59 reference statements)
4
94
0
3
Order By: Relevance
“…An acute event often results in temporary dependence on others. It is important to remember to take advantage of patients` desire to regain independence and incorporate opportunities to involve the patient in their own recovery (Fange and Ivanoff, 2009;Ottenvall Hammar et al 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An acute event often results in temporary dependence on others. It is important to remember to take advantage of patients` desire to regain independence and incorporate opportunities to involve the patient in their own recovery (Fange and Ivanoff, 2009;Ottenvall Hammar et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Older adults are aware of their vulnerability and know that their life situation can suddenly change. They also have a strong inner driving force to maintain their health (Fange and Ivanoff, 2009). Older patients are especially vulnerable to loss of dignity during acute hospital admission because impaired health results in loss of functions and a greater physical dependency.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, it has not been found before that quality of life is equally strongly associated with the home environment and information provision as with physical and mental health factors. Qualitative research provides indications for the enabling role of the home environment: during the aging process the home becomes an increasingly important source of support and independence, compensating for declines in functional capacity (Haak, Fänge, Iwarsson, & Ivanoff, 2007;Fänge & Ivanoff, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the qualitative Swedish data within the ENABLE-AGE Project, have shown that home is a place of meaning (Dahlin-Ivanoff, Haak, Fänge, & Iwarsson, 2007) and perceived as an important place linked to selfperceived health in very old age (Fänge & Dahlin-Ivanoff, 2009). Health was described in terms of being able to manage daily activities at home and participate in broader society.…”
Section: Elsevier_ssm_9267mentioning
confidence: 99%